(untitled) (LTU Journal of Advanced Computing & Engineering, 2026)
Polyherbal mouthwash is an oral preparation formulated with extracts of natural ingredients such as leaves of Neem, the pericarp of Barro, the Betel plant, and the rhizome of Turmeric, along with specific antibacterial agents that show antimicrobial properties. It is applied to maintain oral hygiene, prevent bad breath, and prevent dental and periodontal disease. Polyherbal mouthwash prepared from these plants is used to study their antimicrobial effect against oral pathogens like Staphylococcus aureus, Candida albicans, Escherichia coli, Enterococcus, and Klebsiella, which are commonly found in the oral cavity. The formulation of the polyherbal mouthwash was done by the hydroalcoholic extraction method using a ratio of 1:5 of pulverized powder and solvent (70% alcohol). After the extraction, the mother liquor was evaporated using a water bath at 50°C, and the powder of the active extract of the plant was collected and stored in an airtight container at 2–8 °C. The polyherbal mouthwash was formulated in four different formulations: F1, F2, F3, and F4, in increasing concentrations, respectively. The evaluation of the antimicrobial activity of the formulated polyherbal mouthwash was done by the agar well diffusion method and compared to a commercially available mouthwash (chlorhexidine) as a standard. The zone of inhibition of bacterial growth was measured and compared to the standard. Among the four formulations, F4 had the most effective zone of inhibition: Enterococcus, C. albicans, and S. aureus were 24mm, 26mm, and 18mm, respectively, compared to the standard (chlorhexidine), which were 20mm, 26mm, and 20mm. However, the hydroalcoholic preparation of the polyherbal mouthwash was resistant to E. coli and K. pneumoniae, while the standard was effective toward these bacteria. The formulated mouthwash’s physical properties (color, consistency, odor, pH, density, and viscosity) were also evaluated. The results of this study will provide valuable information on the potential benefits of using a polyherbal mouthwash as part of a daily oral care routine